2021
DOI: 10.1515/cdbme-2021-2108
|View full text |Cite
|
Sign up to set email alerts
|

Dry-fog disinfection as an alternative method for room decontamination

Abstract: Due to the fact that a relatively large area can be disinfected in a short time, dry-fog disinfection could have a great potential to improve hygienic measures. However, there are few studies to date on the effectiveness and combinability of this technology with other devices. In this work, the disinfecting potential of the TBT dry fogging technology (TBT Desinfektion GmbH & Co. KG, Germany) and the corresponding disinfectant Defeat AR (Biofluid GmbH, Germany) was examined with regard to microbiological de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In Which forming fog by the passing liquid through high-pressure nozzles [23]. ULV fogger typically produces that are at least two microns in diameter [26]. Bhul et al [26] reported, in the medical field, an effective infection control strategy has always been critical.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Which forming fog by the passing liquid through high-pressure nozzles [23]. ULV fogger typically produces that are at least two microns in diameter [26]. Bhul et al [26] reported, in the medical field, an effective infection control strategy has always been critical.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ULV fogger typically produces that are at least two microns in diameter [26]. Bhul et al [26] reported, in the medical field, an effective infection control strategy has always been critical. This has been brought into even sharper light by the Corona outbreak.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Which forming fog by the passing liquid through high-pressure nozzles [23]. ULV fogger typically produces that are at least two microns in diameter [26]. Bhul et al [26] reported, in the medical field, an effective infection control strategy has always been critical.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ULV fogger typically produces that are at least two microns in diameter [26]. Bhul et al [26] reported, in the medical field, an effective infection control strategy has always been critical. This has been brought into even sharper light by the Corona outbreak.…”
Section: Literature Reviewmentioning
confidence: 99%